Synthesis of New Indazole Analogs of Curcumin as Antioxidant and Anti-inflammatory Candidates: An In Vitro Investigation - Hariyanti, Hariyanti; Hayun, Hayun; Yanuar, Arry; Azminah, Azminah (Indonesian Journal of Chemistry, 2024)
The development of analog curcumin compounds by modifying the structure of monocarbonyl into an analog indazole of curcumin (AIC) is recognized to have a great potential. Still, only a few reports have been available. Rarely occurring in nature, indazole molecules are typically created through chemical synthesis. Therefore, this study aimed to synthesize six new AIC compounds with a particular focus on testing in vitro antioxidant activity using the DPPH and FRAP methods, as well as anti-inflammatory activity using the protein denaturation method. The results showed that the compounds formed had high anti-inflammatory activity but low antioxidant activity. All synthesis products produced higher anti-inflammatory activity than standard diclofenac sodium and curcumin compounds. Specifically, compound 3a showed the highest anti-inflammatory activity with an IC50 = 0.548 ± 0.062 μM. Therefore, it was concluded that compound 3a has the potential to be further studied for anti-inflammatory activity.